TELAAH KRITIS TERHADAP TEORI PERKEMBANGAN MORAL LAWRENCE KOHLBERG - Nurhayati, Siti Rohmah (Paradigma, 2015)
The theory of moral development from Kohlberg has become a prominent theory and has been widely used to explain individual moral development, as well as a reference in designing the process of moral education. As a theory, Kohlberg’s moral development possesses some strengths as well as weaknesses. Kohlberg divides human moral development into three levels and six phases. Level I is pre-conventional level, consisting of phase 1: Obedience and punishment- anxiety orientation, and phase 2: Egotistical naí¯ve/instrumental hedonism orientation. Level II is conventional level, consisting of phase 3: Good child orientation, and phase 4: Morality of maintaining authority and social regulations. Level III is post-conventional level, consisting of phase 5: Morality of social contract and individual rights, and phase 6: Morality of individual principles and conscience.Kohlberg’s theory constitutes a classical theory of cognitive development, giving an emphasis on integrated characteristic. One strength of Kohlberg’s moral development theory is on the phases of development themselves which make it easier for people to understand moral development. Besides that, this theory shows more on the cross cultural universality compared to other moral development theories. Meanwhile, some notes on the weaknesses of Kohlberg’s theory are: 1) methodologically, the scoring procedure used in this theory is esoteric, subjective, and unstable, thus the results is rather unacceptable for some experts; 2) it is difficult to prove that there is consistent correlations between Kohlberg’s moral development and one’s moral attitudes. The theory proposed by Kohlberg cannot explain about moral excellence because its emphasis is on moral rationality and it tends to ignore character and moral features; 3) although it is considered more universal, the definitions of phases and assumptions on which the theory lays are cultural bias and ethnocentric; 4) the moral reasoning phase of Kohlberg cannot be applied equally between men and women; and 5) Kohlberg’s choice towards one philosophical tradition brings about negative impacts, i.e.: (a) a rigid emphasis on law and fairness; (b) a moral concept which is limited to cognitive aspects, yet pays no attention to feelings, attitude and character, and (c) a failure in using phenomenological perspective from subjective morality experience. Key words : moral development, Kohlberg’s theory